Mechanochemical Defect Engineering of Nb2O5: Influence of LiBH4 and NaBH4 Reduction on Structure and Photocatalysis - Anna Michaely; Elias C. J. Gießelmann; Guido Kickelbick (Solids, 2025)
Partial reduction of transition metal oxides via defect engineering is a promising strategy to enhance their electronic and photocatalytic properties. In this study, we systematically explored the mechanochemical reduction of Nb2O5 using LiBH4 and NaBH4 as reducing agents. Electron paramagnetic resonance (EPR) spectroscopy confirmed a successful partial reduction of the oxide, as seen by the presence of unpaired electrons. Interestingly, larger hydride concentrations did not necessarily enable a higher degree of reduction as large amounts of boron hydrides acted as a buffer material and thus hindered the effective transfer of mechanical energy. Powder X-ray diffraction (PXRD) and 7Li solid-state NMR spectroscopy indicated the intercalation of Li+ into the Nb2O5 lattice. Raman spectroscopy further revealed the increased structural disorder, while optical measurements showed a decreased band gap compared with pristine Nb2O5. The partially reduced samples showed significantly enhanced photocatalytic performance for methylene blue degradation relative to the unmodified oxides.